Empowering Aging with Dignity: The Need for Geriatric Home-based Primary Care in Pakistan - Rabeeya Saeed (Liaquat National Journal of Primary Care)
According to the World Health Organization (WHO), one in six individuals worldwide will be 65 years of age or older by 2030 [1]. Two-thirds of the world’s elderly population, will be living in low- and middle-income countries by 2050 [2]. The number of senior people in Pakistan is predicted to quadruple from 11.3 million to 42.8 million by 2050, representing 12.4% of the country’s total population [3]. With growing and rapid drift in the aging population, the provision of comprehensive, integrated, and accessible primary health care for community-dwelling elderly people is a real challenge for healthcare stakeholders. Traditional clinic-based models, though essential, may not always address the unique needs of senior citizens who live in the community but are isolated from the healthcare system due to frailty, restricted mobility, disease complexity, or social factors. Home-based Primary Care is currently gaining much popularity due to the potential of converting primary care from clinics to home settings. This healthcare model was quite prevalent in the early 20th Century when 40% of the entire medical practice in the US was performed at home [4]. This trend declined sharply after the establishment of hospital centered medical system [4]. However changes in family dynamics and preference to ensure healthcare accessibility within the comfort of home for functionally dependent elderly people led to the rising demand for home-based care in recent years Evidence from developed countries has shown the effectiveness of structured home-based programs which led to significant improvement in patient satisfaction [5]. However, there is a lack of data from developing countries regarding established home-based care models. One of the major advantages of home-based care is convenience. By eliminating the need for travel and waiting time, health care gets accessible within the comfort of a patient’s home. Home-based care is costeffective as it reduces unnecessary hospitalizations and emergency visits, mitigating the financial burden on the patient as well as on the healthcare system [4]. Regular home visits provide an opportunity to assess elderly patients’ living environments, identify potential safety hazards, and offer practical advice on home modifications to enhance independence. This level of individualized attention can help prevent falls, accidents, and other medical complications, which are significant sources of morbidity among the elderly. Home-based primary care is provided by a multidisciplinary team of healthcare professionals, including family physicians, nurses, physical therapists, social workers, mental health counselors, and dietitians. To ensure sustainability and care coordination, efficient diagnostics and pharmacy services, along with a robust referral network, should be in place to support the homebased primary care model. Fig. (1) highlights the scope and framework of the geriatric home-based care model. The landscape of home-based care for the elderly in Pakistan has not yet been thoroughly explored despite the changing need and rising demand [6]. There is an urgent need to establish a nationwide infrastructure of home-based primary care programs in the community, both at the private and government levels. These programs must be linked to tertiary care facilities to guarantee multidisciplinary collaboration and seamless treatment transitions as needed. Comprehensive training programs for healthcare personnel along with financial incentives and a supportive environment, will encourage healthcare professionals to adopt this model. To protect patient safety and public trust, strong regulatory frameworks and quality assurance standards must be developed and implemented. In conclusion, geriatric home-based primary care represents a critical opportunity to enhance the quality of life for older adults and alleviate the burden on hospitals. With thoughtful investment, appropriate policy frameworks, technology integration, and a patient-centered approach, it can play a transformative role in the future of healthcare for aging populations.